A mixed methods evaluation of a Mindfulness-Based Stress Reduction course for people with Parkinson's disease. (November 2017) - Birtwell, Kelly; Dubrow-Marshall, Linda; Dubrow-Marshall, Rod; Duerden, Tim; Dunn, Annette
Abstract: Objective: The aim of this study was to evaluate the effects of an 8-week Mindfulness-Based Stress Reduction course (MBSR) on people with Parkinson's disease who experienced depression, anxiety, stress or difficulty coping with Parkinson's. Methods: Thirteen participants were recruited and six completed the full MBSR course. Data were analysed using repeated measures analysis of variance and thematic analysis. Results: There were significant improvements in levels of depression, anxiety and stress at weeks eight and sixteen, as measured by the Depression Anxiety and Stress Scale, short version (DASS-21). Themes of 'mindfulness as challenging' and 'mindfulness as life-enhancing' were identified from follow-up questionnaire responses. All participants reported they would recommend MBSR to other people with Parkinson's. Conclusion: This study supports previous preliminary findings that mindfulness-based interventions could benefit people with Parkinson's experiencing non-motor symptoms. Further research using larger sample sizes, a control group, and a longer follow-up period is required.